1991
DOI: 10.1111/j.1467-9450.1991.tb00882.x
|View full text |Cite
|
Sign up to set email alerts
|

School performance and IQ‐test scores at age 13 as related to birth weight and gestational age

Abstract: The cohort in the present longitudinal research program consisted of 873 children in an entire school grade, in a Swedish community. The present results showed a main effect of birth weight; low birth weight (LBW) children had lower school performance and intelligence-test (IQ) scores at age 13 than did normal birth weight (NBW) children irrespective of parental SES. Second, there was no significant main effect of gestational age (GA) on scholastic performance and IQ-test scores. Third, there was a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Small reductions in cognitive tests and IQ do not necessarily equate to detectable differences in school performance or children's ability to function in society. In a study of 873 Swedish children, Lagerstrom et al found no significant association between gestational age and either school performance or intelligence scores at 13 y of age [17]. In a study of 5,319 Danish children, parents reported their child's performance at school at 10 y of age [18].…”
Section: Discussionmentioning
confidence: 97%
“…Small reductions in cognitive tests and IQ do not necessarily equate to detectable differences in school performance or children's ability to function in society. In a study of 873 Swedish children, Lagerstrom et al found no significant association between gestational age and either school performance or intelligence scores at 13 y of age [17]. In a study of 5,319 Danish children, parents reported their child's performance at school at 10 y of age [18].…”
Section: Discussionmentioning
confidence: 97%
“…Hack (1998) identified twelve longitudinal observational studies of children between 9 and 17 years of age who were small-for-gestational age (SGA) at birth (Drillien, 1970;Hill, 1978;Westwood et al 1983;Illsey & Mitchell, 1984;Rantakillio, 1988;Hawdon et al 1990;Lagerstrom et al 1991;Low et al 1992;Agarwal et al 1995;Mervis et al 1995;Paz et al 1995;Pryor et al 1995). In all studies the SGA babies had poorer cognition than normal-birth-weight children, although some of the differences were not statistically significant (for example, see Hawdon et al 1990;Agarwal et al 1995).…”
Section: Small-for-gestational Agementioning
confidence: 99%
“…The data strongly support the view that, for males born SGA, it is an advantage to have catch-up growth in length. Several studies indicate that infants born SGA have a higher risk of minimal neurologic dysfunction later in life, reduced mental development potential, and increased risk of subnormal intellectual and psychological performance compared with infants born appropriate for gestational age (1)(2)(3)(4)(5)(6)(7)(8)(9). In these studies, SGA was defined based on low birth weight for gestational age.…”
mentioning
confidence: 99%